Dependência química na adolescência e políticas públicas: um olhar sobre a problemática no municiípio de Santarém-PA - Lauxen, Iarani Augusta Galúcio (2013)
This paper deals with the situation of chemically dependent adolescents in the municipality of Santarém in the state of Pará, observing the institutional indicators pointed out by the Centro de Atendimento Psicossocial Álcool e Drogas- CAPS Ad (Center for Psychosocial Services Alcohol and Drugs) and the Centro Socioeducativo do Baixo Amazonas-CESEBA (Socio-educational Center of Lower Amazonas), as to the cases of registered addicted adolescents and dialogs with the proposal of the existing Public Policies in Brazil for confronting this problem, in the perspective of evaluating their effectiveness in guaranteeing the right to the promotion of mental health for the adolescent who is making improper use of drugs, as these policies relate to the implantation, effectuation and improvement of programs, actions and activities which assure the prevention, treatment, rehabilitation and social reinsertion of these adolescents.